Due di Uno : A composition dedicated to Horacio Vaggione. - Di Scipio, Agostino (Contemporary Music Review, 2005)
At risk of appearing disrespectful in the context of a Festschrift, this article focuses on Due di Uno , a composition of the author's own, dedicated to Horacio Vaggione. This composition reflects an attempt at designing and staging a small technological infrastructure whose audible result is the music. It is an effort in algorithmic composition and, at the same time, an attempt at implementing a network of dynamical interactions between two instruments (piccolo recorder and violin) and live electronics (an adaptive array of digital signal processing transformations). It is, too, a work in sound—that is, a music where timbre, textural polyphony and density, and a variety of noise artefacts are perceptual dimensions more important than others. In addressing such issues, the author keeps Vaggione's own work as a silent, but tangible infratextual reference.